Application of the improved quasi-static coupled probability theory method to transient safety analysis of an experimental facility - Gao, Qingyu; Li, Zhifeng; Zhu, Yuxiang (Frontiers in Energy Research, 2023)
The accelerator-driven sub-critical system is driven by external neutron sources, which are generated by the spallation reaction and maintain the stable operation of the sub-critical core, while the external neutron source increases the complexity of reactor neutron kinetic processes. This article focuses on simulation analysis of neutron space–time kinetics with a dynamic analysis code, which is developed based on the improved quasi-static approximation and Monte Carlo neutron transport method. The amplitude function and shape functions are solved to achieve the dynamics simulation process. Then, the transient responses of beam interruptions and reactivity insertions are calculated and analyzed for an experimental facility. To further verify the correctness and reliability of dynamic behavior, the simulation results are compared with experimental values, and the results show that the normalized neutron fluxes varying with time are in good agreement with the corresponding values. It can be concluded that the improved quasi-static coupled probability theory method can be used to solve the neutron space–time kinetic problem of the experimental facility, and the results are reliable.